EVALUACIÓN DE LOS MATERIALES DIDÁCTICOS EN UNA INSTITUCIÓN DE EDUCACIÓN SUPERIOR EN MÉXICO - Laura Cristina Piñón Howlet; Alma Lilia Sapién Aguilar; María del Carmen Gutiérrez Diez (European Scientific Journal, ESJ, 2013)
In several occasions, the teaching resources are poorly structured because do not follow any instructional design. The objective of this study was to evaluate the teaching resources under two modalities; for a classroom presence and non-classroom presence (distance). The research was conducted in 2008 in the Faculty of Accounting and Administration (FAA) of the Autonomous University of Chihuahua (AUCH) in the cities of Chihuahua, Delicias and Camargo. The study was not experimental, descriptive, and the analysis unit were the teachers and students attending the courses in first through fifth semester in both modalities. A stratified random sampling was used, and the sample size was 1,151 persons (N=1,151) selected randomly. The results showed that for distance learners, the teaching resources were inadequate, while classroom students considered them as acceptable. This teaching modality´s difference confirmed the hypothesis that teaching resources, created for the classroom modality, don't have the same effectiveness as the distance mode. This is for the fact that they are not designed to facilitate learning if the student has no contact with the teacher.